DETERMINATION OF KINETIC ASYMMETRIES IN SOCCER PLAYERS PERFORMING VERTICAL JUMP: PROPOSAL OF A NOVEL PROCEDURE TO DETERMINE IMPULSE FROM FORCE PLATE DATA - Fabíola Bertú Medeiros; Hans-Joachim Menzel; Mauro Heleno Chagas; Gustavo Henrique da Cunha Peixoto Cançado; Silvia Ribeiro Santos Araújo; Fernando Vitor Lima; André Gustavo Pereira de Andrade (Journal of Physical Education)
ABSTRACT The first purpose of this study was to compare the lower limb peak force (Fpeak) asymmetry in two different procedures, simultaneous and sequential, measured in countermovement jump (CMJ) of soccer players. Three series of six CMJ were performed on two force platforms. For the sequential procedure, the 18 CMJ were divided into two blocks of nine attempts. The average of the best three CMJ of the first block was used to determine the Fpeak of a lower limb and the average of three best CMJ of the second block was used to determinate the Fpeak of the other lower limb, and then the order was inverted. In the simultaneous procedure, the mean of Fpeak values of both lower limbs was calculated for all CMJ. The t test did not present significant differences between the procedures in Fpeak asymmetry and there was a significant positive correlation between them (r = .74). The second purpose was to verify the reliability of a new impulse determination procedure for both lower limbs in the CMJ. The partial impulse and impulse asymmetry measurements obtained in this new procedure presented excellent reliability (CCI = .765-.963). It can be concluded that since there was no significant differences between the Fpeak asymmetries values between the two procedures, and the simultaneous procedures also allows the analysis of impulse asymmetry, this procedure would have interesting applications in practical evaluations.